Tingkat Pengembalian Investasi Pendidikan Tinggi Lulusan Program Studi STEM (Science, Technology, Engineering, dan Mathematics) - Perdani, Esti Wahyu; Wicaksono, Padang (Fakultas Ekonomi Universitas Samudra, 2022)
This study aims to analyze the rate of return on investment in higher education for graduates of STEM study programs using data from the 2019 National Labor Force Survey (SAKERNAS). This study uses the Ordinary Least Square (OLS) method with a two-step Heckman approach. The result is that the highest rate of return on investment for STEM graduates occurs at the master's level and the rate of return on investment for female STEM graduates is higher than that of men. STEM study programs have a stereotype, namely study programs with expensive costs and requirements for masculinity, therefore it is necessary to increase the number of scholarships, especially in postgraduate programs and provide equal opportunities for men and women to study and work in the STEM field.